Posterior malleolus fractures in Bosworth fracture-dislocations. A combination not to be missed - Kostlivý, Karel; Bartoníček, Jan; Rammelt, Stefan (Injury, 2020)
OBJECTIVES: Posterior malleolar fractures (PM) have been linked to inferior outcome in malleolar fractures. This study aims to analyze the prevalence and pathoanatomy of PM fractures in Bosworth fracture-dislocations (BF). MATERIALS & METHODS: Radiographs and computed tomography (CT) scans of 13 patients treated at our institution and 97 cases published between 1947 and 2018, identified in a systematic literature search, were evaluated with respect to the pathoanatomy of BF. In all 13 cases from the present study and in 10 cases from the literature, axial CT scans were performed. RESULTS: All 13 patients (100%) with BF from the present series and 61 of 97 documented cases (63%) of BF from the literature were associated with a PM fracture. In patients with a complete CT analysis, dislocation of the fibula behind the posterior tibial rim was associated with extraincisural (Bartoníček / Rammelt type 1) PM fractures. Displacement of the fibula between the displaced PM fragment and the tibia was associated with Bartoníček / Rammelt types 2 and 3 PM fractures. CONCLUSIONS: Seventy prevent of all reported BF are associated with a PM fracture. The true prevalence may be even higher because of the historically infrequent use of CT imaging. The pathoanatomy of the PM fragment is highly variable as is the kind of fibular displacement in BF. Therefore, CT scanning should be performed routinely in BF. Displaced PM fractures in BF involving the incisura should be treated operatively via a direct posterolateral approach.
Keywords: Imaging, Three-Dimensional; počítačová rentgenová tomografie; Locked dislocation; Ankle Fractures; Humans; fraktury tibie; lidé středního věku; Tibial Fractures; Fibula; Fracture Dislocation; fraktury kotníku; Female; Aged; mladý dospělý; dospělí; Posterior malleolus; senioři; lidé; tarzální kosti; Ankle fracture-dislocation; Maisonneuve fracture; Adult; Syndesmosis; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; Young Adult; zobrazování trojrozměrné; fibula; dislokovaná fraktura; mužské pohlaví; Tarsal Bones